2017
DOI: 10.2214/ajr.16.17602
|View full text |Cite
|
Sign up to set email alerts
|

CNS Injuries in Abusive Head Trauma

Abstract: AHT is a frequent cause of neurologic injury in children, particularly in infants in the first year of life. Imaging evaluation plays a vital role in determining the diagnosis and prognosis. A review of the intracranial injuries that are common in AHT cases has been provided. Understanding the common patterns of abusive head injury can help increase diagnostic accuracy both by increasing recognition of injuries with a high specificity for AHT and by avoiding unwarranted concern in patients with concordant inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 102 publications
0
27
0
2
Order By: Relevance
“…However, it seems that no fracture pattern is diagnostic for abuse. It is known that multiple, complex, diastatic, depressed, and growing fractures suggest a high-energy mechanism and are therefore suspicious for AHT in the absence of an appropriate clinical history (Fig 1) ( [11][12][13]. Occipital bone fractures are also more commonly seen with AHT (14).…”
Section: Skull Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it seems that no fracture pattern is diagnostic for abuse. It is known that multiple, complex, diastatic, depressed, and growing fractures suggest a high-energy mechanism and are therefore suspicious for AHT in the absence of an appropriate clinical history (Fig 1) ( [11][12][13]. Occipital bone fractures are also more commonly seen with AHT (14).…”
Section: Skull Fracturesmentioning
confidence: 99%
“…A wide spectrum of parenchymal imaging findings can be seen in the brain in patients with SDH and bridging vein thrombosis. Additional parenchymal changes often increase the specificity for abusive trauma and enable accurate prognostication (13). The sensitivity of MRI is much higher for detecting these injuries when compared with that of CT alone (14).…”
Section: Parenchymal Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…10e12 A recent comprehensive review of the neuroradiological findings associated with AHT has been published by Wright. 13 In conjunction with clinical examination, neuroradiological investigations, predominantly computed tomography (CT) and magnetic resonance imaging (MRI) play a complementary role with each modality having its own benefits and limitations. 14…”
Section: Introductionmentioning
confidence: 99%
“…24 The characteristics of SDH associated with AHT, both acute and subacute has been reviewed comprehensively recently. 13 Findings from systematic reviews have demonstrated that the presence of epidural haemorrhage in the context of an isolated skull fracture and scalp swelling is significantly associated with accidental head trauma. 24,25 Subarachnoid haemorrhage as a solitary finding is non-discriminatory.…”
mentioning
confidence: 99%